Pénzintézeti szolgáltatók jelenléte dráván innen és túl (Presence of Financial Servicers Along River Drava) - Sándor Zsolt Kovács (DETUROPE)
The economic role of financial services in the national economy is unquestionable, so the examination of these services is a relevant theme during the survey of the state of a region, county or other territorial unit. In this study we examine an unofficial administrative region which is an important geographical area in the development programme of the EU (Hungary–Croatia IPA Cross-border Programme). The aim of this paper is the introduction of some indicators of bank networks in Croatia and Hungary especially their joint border region, such as availability, financial exclusion, and economic share of financial services. We evaluate these indicators according to the international standards and best practices.